Spirituality at workplace and its impact on academic performance: an empirical study among private higher education faculties of Delhi NCR - Sapra, Jayashree; Khosla, Khushboo; Dungrakoti, Garima (Journal of organizational change management, 2022)
PurposeThe impact of workplace spirituality on organizational performance has continued to draw the attention of scholars and practitioners. Despite this enhanced attention, little is known about its the impact on academic performance. Addressing this gap in research, the purpose of this study is to empirically examine the impact of spirituality at workplace on academic performance among private sector higher education faculties in Delhi NCR.Design/methodology/approachThis study outlines the existing literature on workplace spirituality and academic performance and its relationship. The scale created by Petchsawang and Duchon (2009) has been used to measure workplace spirituality, whereas academic performance of faculties was measured by the scale created by Abubakar et al. (2018). Pearson correlation and linear regression have been used to depict the degree of relation and impact of spirituality on academic performance.FindingsThis study provides evidence that by practicing workplace spirituality, the performance of higher education faculties can be positively and significantly impacted. The result reflects that in the presence of compassion, mindfulness, meaningful work and transcendence, the academic organizational performance of higher education institutes is improved as there will be an enhancement in their academic reputation, employability of the graduate students, research work, internationalization, Nobel-prized and field medals, research grant, resources, infrastructure and community services.Research limitations/implicationsThe results of this study are subject to certain limitations, which can be addressed in future studies. Only four dimensions of workplace spirituality, i.e. compassion, mindfulness, meaningful life and transcendence, are taken into consideration. Also, the impact has only be studied on academic performance of higher education institutions. The results of this study cannot be used in a generalized context as the framework of this study is based on higher education faculties in Delhi NCR.Practical implicationsThe findings of this study would be a roadmap for higher education institutions or their faculties to improve performance with the assistance of spirituality at workplace.Social implicationsRetention of academic personnel is critically necessary so that the excellence of higher education is maintained. It is the need of the hour for these educational institutions to be more focused on improving the teaching staff efficiency. This is made possible through the development of an atmosphere that installs spirituality. The empirical findings of this research will enable academics as well as managers to understand how and to what degree faculties experience spirituality at workplace and its association with different outcomes.Originality/valueIndia's higher education higher education system is the third largest in the world, next to the USA and China. India's higher education system has expanded steadily, and India has over 1,000 universities as of 2020. Workplace spirituality for academicians is under-researched and neglected by organizations. It may further benefit those interested in employment learning.